The Meaning and Application of the Qur'an for the Peace of Human Life in Building a Peaceful and Meaningful Life - Uus Husni Hoer; Fikri Abdillah Azam; Agus Setiyawan; M Abdurrahman; M Wildan Nur Fadhilah (Penerbit Hellow Pustaka, 2025)
The Quran is a guide to life, a source of inner peace for humans. In modern life, characterized by stress, anxiety, and a loss of spiritual direction, the values ​​of the Quran offer a genuine solution. This article examines the concept of peace from a Quranic perspective using a thematic interpretation (maudhu'i) approach. Analysis of several verses shows that peace (as-sakinah and ath-thuma'ninah) is achieved through faith, dhikrullah (remembrance of Allah), tawakkul (trust in God), and a balance between worldly and afterlife aspects. This study utilizes classical and contemporary sources of interpretation, such as those by Ibn Kathir, Quraish Shihab, and M. Yunan Yusuf. The results indicate that the stronger a person's spiritual connection with the Quran, the greater the peace they experience.